Nilai-nilai Moral dalam Tradisi Robo-robo di Desa Punggur Kapuas Kecamatan Sungai Kakap Kabupaten Kubu Raya - Syarifah Shalwa Farisha (Jurnal Inovasi Pendidikan dan Pengajaran (JIPP), 2023)
Â In general, this research is to explain the moral values contained in the robo-robo tradition in Punggur Kapuas Village, Sungai Kakap Districth. The type of research used is descriptive research with a qualitative approach. Data collection was carried out through interviews and document study techniques. The tools used for data collection were interviev guides and documents. Data analysis uses an interactive data analysis model. The result of this study include moral values related to other human beings, and moral values related to God.